PENGARUH ESG, KINERJA KEUANGAN, LEVERAGE, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Sinaga, Meilani; Darsono, Darsono (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG), financial performance, leverage, liquidity, and firm size on firm value in Indonesia. Firm value reflects investors’ perceptions of a company’s success, which is generally associated with stock prices and overall company performance. These perceptions are influenced by various factors, including non-financial aspects such as ESG as well as financial factors such as profitability, capital structure, liquidity, and firm size, making it important to analyze them empirically.This study employs a documentation method using secondary data obtained from companies’ financial statements. The sample consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2024. Based on purposive sampling criteria, a total of 118 firm-year observations were selected. The data analysis technique applied in this study is panel data regression.The results show that financial performance and leverage have a positive effect on firm value. Meanwhile, Environmental, Social, and Governance (ESG), liquidity, and firm size do not have a significant effect on firm value. These findings indicate that investors tend to place greater emphasis on financial performance and capital structure rather than other factors in assessing firm value.